2020
DOI: 10.1146/annurev-neuro-091619-022657
|View full text |Cite
|
Sign up to set email alerts
|

Neuropod Cells: The Emerging Biology of Gut-Brain Sensory Transduction

Abstract: Guided by sight, scent, texture, and taste, animals ingest food. Once ingested, it is up to the gut to make sense of the food's nutritional value. Classic sensory systems rely on neuroepithelial circuits to convert stimuli into signals that guide behavior. However, sensation of the gut milieu was thought to be mediated only by the passive release of hormones until the discovery of synapses in enteroendocrine cells. These are gut sensory epithelial cells, and those that form synapses are referred to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 114 publications
2
75
0
3
Order By: Relevance
“…Cholecystokinin is secreted from enteroendocrine cells in the upper small-intestinal epithelium when nutrients arrive in the lumen, and transmits satiation signals to the brain by interacting with cholecystokinin A receptors on the afferent vagus nerve [30,40,[47][48][49][50] and possibly the brain [51,52]. Bohorquez and colleagues recently characterized enteroendocrine cells (i.e., neuropods) in the mouse intestinal epithelium that form functional synapses with afferent vagal fibers [33]. Neuropods sense nutrients in the lumen and in response, release glutamate and cholecystokinin, which activate afferent vagal neurons in a coordinated manner [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholecystokinin is secreted from enteroendocrine cells in the upper small-intestinal epithelium when nutrients arrive in the lumen, and transmits satiation signals to the brain by interacting with cholecystokinin A receptors on the afferent vagus nerve [30,40,[47][48][49][50] and possibly the brain [51,52]. Bohorquez and colleagues recently characterized enteroendocrine cells (i.e., neuropods) in the mouse intestinal epithelium that form functional synapses with afferent vagal fibers [33]. Neuropods sense nutrients in the lumen and in response, release glutamate and cholecystokinin, which activate afferent vagal neurons in a coordinated manner [53].…”
Section: Discussionmentioning
confidence: 99%
“…Nutrients are sensed by gustatory cells in the oral cavity and enteroendocrine cells in the intestinal epithelium. In response, these cells release several satiation-and satiety-related molecules that communicate with the brain via a mechanism that includes the afferent vagus nerve [30][31][32][33][34][35][36][37][38]. We recently reported that eCB signaling in the gut controls nutrient-induced release of satiation peptides [16].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropods are basal processes of EECs that contain large, dense vesicles of gut peptides and small, clear vesicles containing neurotransmitters [ 27 , 28 ]. These features extend into the lumen and interact with vagal neurons via release of vesicle contents for rapid signal transduction to the brain [ 29 ]. Thus, the interaction of gut peptides with the gut–brain axis orchestrates metabolic function, communicates nutrient status to the brain and modulates central-regulated appetite and homeostatic processes, which together drive food seeking and eating behaviour, to maintain energy balance.…”
Section: Gastrointestinal Peptides and The Gut–brain Axismentioning
confidence: 99%
“…These highly heterogeneous enteroendocrine subtypes facilitate specific metabolic and immune responses to different inputs from ingested nutrients, irritants, pathogens, etc. (Kaelberer et al, 2020;Yu et al, 2020). To investigate the potential mechanisms that control enteroendocrine cell diversification, a recent study combined scRNA-seq technique and the expression of fluorescent timer proteins in the enteroendocrine lineage.…”
Section: Beyond Pnecs: Epithelial Cells With Sensory and Secretary Fumentioning
confidence: 99%